Lifetime sensitivity analysis of FPSO operating parameters on energy consumption and overall oil production in a pre-salt oil field - Allahyarzadeh-Bidgoli, Ali; Dezan, Daniel Jonas; Salviano, Leandro Oliveira [UNESP]; Oliveira Junior, Silvio de; Yanagihara, Jurandir Itizo (Taylor & Francis Inc, 2019)
Floating production storage and offloading (FPSO) platforms are great energy consumers. Reservoir fluid composition and operating parameters of FPSOs are known to be important parameters for the total energy demand, and also for enhancing overall oil production. In the current research paper, the contribution of eight thermodynamic input parameters of a typical Brazilian FPSO operating on a pre-salt field is quantified by the Smoothing Spline ANOVA method for two responses: (i) energy consumption of the plant and; (ii) overall oil production. Three operation modes are considered in the analysis: Mode 1 (maximum oil/gas content), Mode 2 (50% BS&W) and Mode 3 (maximum water/CO2 content). The input parameters considered in the present research are: output pressure of the first control valve (P-1), output pressure of the second stage of separation train (P-2), input pressure of the third stage of separation train (P-3), output pressure of dilution water pump (P-4), output pressure of the main gas compressor (P-c), petroleum temperature of the first heat exchanger (T-1), petroleum temperature of the second heat exchanger (T-2), and dilution water temperature of heat exchanger (T-3) are considered as input parameters. In terms of energy consumption, parameters P-3 and P-c are always relevant for all operation modes. Furthermore, P-3, P-2, and T-2 are the most important parameters for overall oil production for all operation modes.
Keywords: Energy efficiency; FPSO; Oil and gas processing plant; Pre-salt oil field; Sensitivity analysis; Smoothing spline ANOVA method